Implementation Analysis of the Youth Posyandu Program in Pekalongan City - Eltanin Kumala Dewi; Sutopo Patria Jati; Antono Suryoputro (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze the implementation of the Youth Posyandu/Integrated Health Post program in Pekalongan city. The research design used qualitative with in-depth interview techniques and data triangulation. The informants consisted of relevant officials, Posyandu cadres, and stakeholders. The results indicate that strategies for increasing youth participation include intensifying education, involving community leaders, creating a youth-friendly atmosphere, and strengthening the role of cadres. The barriers to participation can be resolved through a creative and collaborative approach. Adolescents' health awareness is increased through understanding their needs. Health information was delivered using an attractive digital platform according to teenagers' interests. Overcoming access barriers required stigma-free educational campaigns, supportive environments, and active youth involvement. The positive role of parents and the social environment creates norms that support adolescent participation. A youth-friendly environment was created through participatory design, adequate facilities, and organizing activities by teenagers. Moreover, evaluation of program effectiveness involved measurable performance indicators, comprehensive data analysis, and ongoing feedback to optimize impact on youth knowledge, behavior, and well-being.